Analisis Pengendalian dan Pengawasan Intern Sistem Penerimaan dan Pengeluaran Kas pada Organisasi Keagamaan (Studi Kasus pada Jemaat Gmim Kyrios Wangurer): Penelitian - Meilany Kesek (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine whether the internal control of the cash receipts and disbursements system in the religious organization of the Evangelical Church in Minahasa is in accordance with the components of internal control according to the Committee of Sponsoring Organizations of the Treadway Commission (COSO). This research is important so that the GMIM kyrios congregation can understand and evaluate the internal controls on the cash receipts and disbursements system that has been implemented. This type of research is a case study of the Kyrios GMIM congregation. The data collection techniques used are interviews, observation and documentation. The data analysis technique used is descriptive analysis. The results of this study indicate that the existing internal control at GMIM Kyrios is not fully in accordance with the five components of control according to COSO, the components that are not yet in accordance are the Control Environment component, the Risk Assessment component and the Control Activity component.